"Anaerotruncus massiliensis, " a new species identified from human stool from an obese patient after bariatric surgery. (November 2016) - Togo, A.H.; Valero, R.; Delerce, J.; Raoult, D.; Million, M.
Abstract: We report the main characteristics of a new bacterial species strain AT3 T (CSUR = P2007, DSM = 100567) that was isolated from the stool sample collected from a 47-year-old obese French man after he underwent bariatric surgery.